Phentolamine rescue for glanular ischemia in the setting of inadvertent administration of high-dose 1:1,000 epinephrine to glans in distal hypospadias surgery - Victoria Schulte; Alexandra Carolan; Irina Stanasel; Bruce Schlomer (Urology Case Reports)
Low-dose 1:100,000 epinephrine is often injected into the glans penis during hypospadias surgery as a vasoconstrictive agent to reduce bleeding and assist with surgeon visualization. In this case, high-dose 1:1000 epinephrine was inadvertently injected into the glans, resulting in persistent tissue ischemia that did not resolve with conservative measures. Injection of phentolamine, an alpha-adrenergic antagonist, into the glans penis was successful in reversing the ischemia. In addition to demonstrating usefulness of phentolamine in this situation, this case also demonstrates the necessity for good communication in the operating room and the need for processes to ensure safe administration of high-risk medications.